2015
DOI: 10.1186/s12868-015-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of hippocampal glutamatergic receptors in neuropathic anxiety-like behavior after partial sciatic nerve ligation in rats

Abstract: Background: Neuropathic pain evoked by nerve injury is frequently accompanied by deterioration of emotional behaviors, but the underlying signaling mechanisms remain elusive. Glutamate (Glu) is the major mediator of excitatory synaptic transmission throughout the brain, and abnormal activity of the glutamatergic system has been implicated in the pathophysiology of pain and associated emotional comorbidities. In this study we used the partial sciatic nerve ligation (PSNL) model of neuropathic pain in rats to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 66 publications
6
28
1
Order By: Relevance
“…However, there are conflicting reports on the effects of pain on natural food rewards, including sucrose preference, with some studies demonstrating decreased sucrose consumption [1; 48; 50; 81; 93; 99] while others show no change [66; 76; 94]. A study by Schwartz and colleagues used mice with sciatic nerve injury-induced neuropathic pain or CFA-induced inflammation and demonstrated that even though injured animals showed no deficits in sucrose preference, they displayed decreased motivation for food reward in a progressive ratio operant responding task [76].…”
Section: Impact Of Chronic Pain On Motivational and Hedonic Componentmentioning
confidence: 99%
“…However, there are conflicting reports on the effects of pain on natural food rewards, including sucrose preference, with some studies demonstrating decreased sucrose consumption [1; 48; 50; 81; 93; 99] while others show no change [66; 76; 94]. A study by Schwartz and colleagues used mice with sciatic nerve injury-induced neuropathic pain or CFA-induced inflammation and demonstrated that even though injured animals showed no deficits in sucrose preference, they displayed decreased motivation for food reward in a progressive ratio operant responding task [76].…”
Section: Impact Of Chronic Pain On Motivational and Hedonic Componentmentioning
confidence: 99%
“…However, pain-induced alterations in responses to natural food rewards, including sucrose preference, have been variable, with some studies reporting decreased sucrose consumption [1; 23; 24; 42; 46; 49] or no change [39; 48]. Although no deficits were observed in sucrose preference in mice with either sciatic nerve injury-induced neuropathic pain or CFA-induced inflammation, decreased motivation for food reward using operant responding has been observed [39].…”
Section: Introductionmentioning
confidence: 99%
“…Behavioural alterations have been described in rat models of peripheral traumatic nerve injury (Hu et al., 2007; Blackbeard et al., 2012; Galan‐Arriero et al., 2015; Wang et al., 2015; Avila‐Martin et al., 2015; Grégoire et al., 2012), neuropathic viral infection (Hasnie et al., 2007; Wallace et al., 2007a) and drug‐induced neuropathies (Wallace et al., 2007b; Huang et al., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…In animal models, the effect of nociceptive stimuli on the affective and cognitive experience can be approximated using ethologically relevant behaviours such as burrowing (Andrews et al, 2012) and thigmotaxis (Huang et al, 2013). Behavioural alterations have been described in rat models of peripheral traumatic nerve injury (Hu et al, 2007;Blackbeard et al, 2012;Galan-Arriero et al, 2015;Wang et al, 2015;Avila-Martin et al, 2015;Gr egoire et al, 2012), neuropathic viral infection (Hasnie et al, 2007;Wallace et al, 2007a) and drug-induced neuropathies (Wallace et al, 2007b;Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%